1999
DOI: 10.1093/ps/78.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Comparative testing of anticoccidials in broiler chickens: the role of coccidial lesion scores

Abstract: The relationship between oocyst dose and lesion score was evaluated in trials involving five field isolates each of Eimeria acervulina, Eimeria maxima, and Eimeria tenella. Each trial included an uninfected, unmedicated treatment, and at least three treatments of unmedicated birds given different doses of oocysts from a single isolate. In four trials each with E. acervulina and E. tenella, and all five trials with E. maxima, infected, salinomycin-medicated (60 ppm) treatments were included. Each treatment cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 15 publications
3
41
0
Order By: Relevance
“…C. jejuni was identified in the used litter and the ileal digesta of challenged birds at 22 days of age, while the control digesta was negative for C. jejuni. The Eimeria oocyst count from the used litter was 27,000 oocyst per gram which corresponds to lesion score 1 [19]. This oocyst count was within the expected range for a poultry unit at 35 days.…”
Section: Resultssupporting
confidence: 51%
“…C. jejuni was identified in the used litter and the ileal digesta of challenged birds at 22 days of age, while the control digesta was negative for C. jejuni. The Eimeria oocyst count from the used litter was 27,000 oocyst per gram which corresponds to lesion score 1 [19]. This oocyst count was within the expected range for a poultry unit at 35 days.…”
Section: Resultssupporting
confidence: 51%
“…Similarly, LivaCox® contained attenuated lines of Eimerian parasites that may have produced lesions in vaccinated chickens and unable to decrease lesions in 100% of the immunized chickens. These results demonstrated that mild to moderate lesions were produced despite immunity conferred due to LivaCox® vaccination which reflects that the coccidian parasites multiplied but may not lead to fatality to cause the disease (Conway et al 1990, Conway et al 1993and Conway et al 1999.…”
Section: Resultsmentioning
confidence: 86%
“…However, the fact that in the first study a higher inoculation dose was used may have, at least in part, further compromised the effectivity of the anticoccidial drugs tested. Conway et al (1999) have shown a dose effect on the lesion score of unmedicated and salinomycin-medicated chickens; higher lesion scores occurred in both categories if a higher inoculation dose was used.…”
Section: Discussionmentioning
confidence: 93%